The Contribution of Music Education to Character Development in Elementary Schools - Tulad Sutomo; Fitrawati Fitrawati (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Music education plays a crucial role in supporting the cognitive, affective, and psychomotor development of elementary school students. This study aims to analyze the contribution of music learning to students' thinking skills and identify other developmental aspects that can be enhanced through musical activities. This study employed a qualitative literature review, drawing on relevant scientific articles. The findings indicate that music education in elementary schools can foster and shape students' character values. Teachers can discover students' interests and talents. Furthermore, repeated training can foster cognitive, affective, and psychomotor aspects, as well as implement positive activities for students. This finding is in line with (Madina Ameliza, Hakim Ardipal, Miaz Ramalis, 2021) They said that music education, as a branch of arts education, plays a vital role in fostering the holistic development of students. Music enhances the cognitive, affective, and psychomotor domains, and serves as a medium for aesthetic expression and emotional refinement.